2004
DOI: 10.4049/jimmunol.173.3.1519
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Antigen-Specific Immunity by CD95 Ligand (Fas Ligand) and IL-10

Abstract: Following elimination of a foreign invader, the immune system must return to its normal quiescent levels. This process requires removal of reactive immune cells when they are no longer needed. We have explored the role of Fas/Fas ligand (FasL) in terminating immunity and demonstrate that mice defective in these proteins have prolonged immune responses. Studies demonstrate that termination of immunity occurs via the interaction of Fas+ lymphoid cells with FasL+ nonlymphoid cells at the site of Ag challenge. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…The high levels of FasL in Fasdeficient lpr mice were shown to eliminate transferred T cells in other models (28,33), and T cells from WT NOD donors were selectively eliminated by FasL-expressing, double-negative host cells in NOD-lpr recipients after adoptive transfer, presumably accounting for their failure to infiltrate host islets and induce diabetes (16). These results are consistent with those reported in this study and suggest that increased FasL expression by lymphoid or nonlymphoid tissues can protect such tissues from damage and limit the duration of immune responses by inducing apoptosis of infiltrating Fas ϩ cells (35,36,38,39). In summary, our results indicate that apoptosis involving the Fas-FasL pathway is critically involved in G-EAT resolution.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high levels of FasL in Fasdeficient lpr mice were shown to eliminate transferred T cells in other models (28,33), and T cells from WT NOD donors were selectively eliminated by FasL-expressing, double-negative host cells in NOD-lpr recipients after adoptive transfer, presumably accounting for their failure to infiltrate host islets and induce diabetes (16). These results are consistent with those reported in this study and suggest that increased FasL expression by lymphoid or nonlymphoid tissues can protect such tissues from damage and limit the duration of immune responses by inducing apoptosis of infiltrating Fas ϩ cells (35,36,38,39). In summary, our results indicate that apoptosis involving the Fas-FasL pathway is critically involved in G-EAT resolution.…”
Section: Discussionsupporting
confidence: 89%
“…For example, FasL expression by cells in the CNS is important for spontaneous remission in EAE (14,15), and expression of FasL by nonlymphoid tissues or in immunologically privileged sites such as the eye can promote the survival of these tissues after injury or inflammation (34 -37). A critical role for FasL expression by nonlymphoid cells in termination of immune responses to foreign Ags has also been demonstrated (38). In our studies depletion of CD8 ϩ T cells in WT recipients inhibited G-EAT resolution, and FasL expression in thyroids was reduced.…”
Section: Discussionsupporting
confidence: 69%
“…Co-modulation of surface receptors is a preceding event of T cell apoptosis (31) and involves the CD95/CD95L system (10). Because M⌽ express and secrete CD95L (32) and IL-10 is capable of up-regulating CD95L (33), it is conceivable that neonatal M⌽ do not primarily destroy lymphocytes that exhibit (auto)antibodies on their surface, but may form conjugates with nonlymphoid antibody-reactive tissues and induce apoptosis (34). Increased CD95L concentrations were found in healthy neonates (35) and maternal or neonatal inflammatory diseases (36).…”
Section: Discussionmentioning
confidence: 99%
“…Although as in the nervous system the mechanism has not yet been fully elucidated, we have suggested that one way in which mercury may be associated with autoimmune disease is through interference with the CD95 signaling pathway. Disruption of CD95 signaling is well known to have detrimental pro-inflammatory and autoimmune consequences (Strasser et al ., 2004; Barreiro et al ., 2004; Krueger et al ., 2003), and we have reported that both in vitro and in vivo , low level exposures to mercury leading to environmentally relevant mercury burdens on T cells result in diminished CD95 signaling (Whitekus et al ., 1999; McCabe, Jr. et al ., 2005a; Laiosa et al ., 2007). While the targets of mercury are not necessarily the same in the immune and nervous systems, we conjectured that in general n-3 PUFAs might counter the negative effect of low level Hg in the immune system as they seem to do in the nervous system.…”
Section: Introductionmentioning
confidence: 99%